Human Trafficking in the Qur'an: A Review of the Meaning of Feminist Interpretation - Imaduddin; Atian Panji Mujahid (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Society and state are often used as the dominant object of human trafficking mafia syndicates (trafficking in persons). The modus operandi is also various, ranging from violent exploitation such as being employed as a sex worker (online or ordinary), cyber crime, marriage with a foreign man for the purpose of exploitation and illegal drug dealers, a matchmaking agency that is considered to be under the guise of sharia, and a serial marriage service provider, and even trafficking women with the modus operandi umrah. The purpose of this research is to discuss feminist interpretations of verses that hint at Human Traffickiing. The method carried out in this study is library research. The results of this research can be used to prevent the occurrence of Human Trafficking.